"Secadores de la fábrica de contrachapeado No. 1 (Sección Forestal)". Series of 2 photos. Copied from CNT collection
"Secadores de la fábrica de contrachapeado No. 1 (Sección Forestal)". Series of 2 photos. Copied from CNT collection.